Immediate effects of yoga breathing with intermittent breath holding on response inhibition among healthy volunteers - Apar Avinash Saoji; B R Raghavendra; S K Rajesh; N K Manjunath (International Journal of Yoga, 2018)
Background: There is very little evidence available on the effects of yoga-based breathing practices on response inhibition. The current study used stop-signal paradigm to assess the effects of yoga breathing with intermittent breath holding (YBH) on response inhibition among healthy volunteers. Materials and Methods: Thirty-six healthy volunteers (17 males + 19 females), with mean age of 20.31 ± 3.48 years from a university, were recruited in a within-subject repeated measures (RM) design. The recordings for stop signal task were performed on three different days for baseline, post-YBH, and post yogic breath awareness (YBA) sessions. Stop-signal reaction time (SSRT), mean reaction time to go stimuli (go RT), and the probability of responding on-stop signal trials (p [r/s]) were analyzed for 36 volunteers using RM analysis of variance. Results: SSRT reduced significantly in both YBH (218.33 ± 38.38) and YBA (213.15 ± 37.29) groups when compared to baseline (231.98 ± 29.54). No significant changes were observed in go RT and p (r/s). Further, the changes in SSRT were not significantly different among YBH and YBA groups. Conclusion: Both YBH and YBA groups were found to enhance response inhibition in the stop-signal paradigm. YBH could be further evaluated in clinical settings for conditions where response inhibition is altered.